Answer:
![\large\boxed{B.\ (f+g)(x)=2x^2+2x-2}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7BB.%5C%20%28f%2Bg%29%28x%29%3D2x%5E2%2B2x-2%7D)
Step-by-step explanation:
![f(x)=-x^2+6x-1\\\\g(x)=3x^2-4x-1\\\\(f+g)(x)=f(x)+g(x)\\\\\text{substitute:}\\\\(f+g)(x)=(-x^2+6x-1)+(3x^2-4x-1)\\\\(f+g)(x)=-x^2+6x-1+3x^2-4x-1\qquad\text{combine like terms}\\\\(f+g)(x)=(-x^2+3x^2)+(6x-4x)+(-1-1)\\\\(f+g)(x)=2x^2+2x-2](https://tex.z-dn.net/?f=f%28x%29%3D-x%5E2%2B6x-1%5C%5C%5C%5Cg%28x%29%3D3x%5E2-4x-1%5C%5C%5C%5C%28f%2Bg%29%28x%29%3Df%28x%29%2Bg%28x%29%5C%5C%5C%5C%5Ctext%7Bsubstitute%3A%7D%5C%5C%5C%5C%28f%2Bg%29%28x%29%3D%28-x%5E2%2B6x-1%29%2B%283x%5E2-4x-1%29%5C%5C%5C%5C%28f%2Bg%29%28x%29%3D-x%5E2%2B6x-1%2B3x%5E2-4x-1%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C%28f%2Bg%29%28x%29%3D%28-x%5E2%2B3x%5E2%29%2B%286x-4x%29%2B%28-1-1%29%5C%5C%5C%5C%28f%2Bg%29%28x%29%3D2x%5E2%2B2x-2)
Your answer will be 406 hope this helps
Answer:
9 square units
Step-by-step explanation:
1/2(3)=1.5
1/2(6)=3
2
1/2(3)=1.5
1/2(2)=1
1.5+1.5+3+2+1=9
Answer:
q = log4 / log0.53
q = -2.189
Step-by-step explanation:
(0.53)^q = 4
Taking log of both sides!
q log 0.53 = log 4
q = log 4 / log 0.53
q = 0.602 / -0.275
q = - 2.189
This can be checked to confirm correctness.
Substituting q = -2.189
(0.53)^ -2.189 = 1/ 0.249
= 4.01 Proved!
(Note that the "1" is because of the negative sign)
Answer:
52
Step-by-step explanation:
plug in 3 if we're going by 0,1,2,3
2+ (3-1)25
2+50
52